2020
DOI: 10.1007/s42770-020-00274-5
|View full text |Cite
|
Sign up to set email alerts
|

Feline sporotrichosis in Asia

Abstract: Sporothrix schenckii sensu lato is currently recognized as a species complex with only Sporothrix brasiliensis, Sporothrix schenckii sensu stricto, Sporothrix globosa and Sporothrix pallida identified to cause disease in the cat. Feline sporotrichosis in Asia is mainly reported from Malaysia where a single clonal strain of clinical clade D, Sporothrix schenckii sensu stricto manifesting low susceptibility to major antifungal classes, has been identified as the agent of the disease. Sporothrix globosa has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 54 publications
0
15
0
3
Order By: Relevance
“…Among the new pathogenic species, S. brasiliensis has the higher clinical-epidemiological impact (4,5) as the main species related to cat to human transmission in South America (6)(7)(8), while S. schenckii has a worldwide distribution (5). In addition, S. brasiliensis is the prevalent species related to sporotrichosis in cats (Felis catus domesticus) followed by S. schenckii (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Among the new pathogenic species, S. brasiliensis has the higher clinical-epidemiological impact (4,5) as the main species related to cat to human transmission in South America (6)(7)(8), while S. schenckii has a worldwide distribution (5). In addition, S. brasiliensis is the prevalent species related to sporotrichosis in cats (Felis catus domesticus) followed by S. schenckii (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…These data suggested that the analyzed inoculum size of conidia is not able to show differences in the animal mortality associated with the different fungal species, nor the 1×10 7 yeast-like cell inoculum, but fungal challenges of 1×10 5 or 1×10 6 yeast-like cells were capable of killing the animal population similarly as reported in mice and G. mellonella larvae, keeping the previously reported virulence rank, ie, S. brasiliensis as the fastest species to kill the host and S. globosa the slowest. Therefore, we continued our analysis only with animals inoculated with either 1×10 5 or 1×10 6 yeastlike cells.…”
Section: Sporothrix Spp Kills Tenebrio Molitor Larvae In a Dose-dependent Mannermentioning
confidence: 95%
“…[1][2][3] This infection is traditionally considered as a sapronosis, where decaying vegetal tissues are the natural niche for fungal growth; 1 however, due to the recent increment in animal sporotrichosis cases, particularly in domestic species, this disease is also now considered as a zoonosis. [4][5][6] Most of the cases positively respond to the conventional antifungal therapies or are fixed lesions that are controlled by the host immunity, but there is the risk to develop a life-threatening systemic infection, which in recent years is increasing in frequency, in particular in immunosuppressed patients. 7 Sporothrix schenckii, Sporothrix brasiliensis, and Sporothrix globosa are the three out of the 51 species classified within the Sporothrix genus that are the etiological agents of most of the animal and human sporotrichosis cases and are grouped within the pathogenic clade of this genus.…”
Section: Introductionmentioning
confidence: 99%
“…The species S. globosa is the most common in human cases in Asia and America, and in Europe the first autochthonous was reported in Portugal [15][16][17]. The species S. schenckii sensu stricto predominate in humans in Australia, South Africa, western South and Central America, and North America and is the only species described in cats in Malaysia [18]. The species S. mexicana is most commonly isolated from environment and rarely reported in human clinical cases in Brazil [19] and Portugal [5].…”
Section: Introductionmentioning
confidence: 99%